AN ANALYSIS OF SOCIAL CLASS AND DISCRIMINATION IN JUAN SOLANAS’ MOVIE “UPSIDE-DOWN” - Muhammad Ali; Iskandar Iskandar; La Sunra La Sunra (State University of Makassar, 2023)
Social Class and Discrimination are social problems that live and are rooted in a social group. Social class is a division of groups with attributes in the form of wealth, power, and education, while discrimination is an act that harms individuals and groups. Then what is meant by social class and discrimination in the film “Upside-Down” by Juan Solanas, and what are the effects of social class and discrimination? In the division of social class, there are several divisions of groups that have an impact in the form of discrimination that occurs. The purpose of this study is to provide an explanation of what is meant by social groups and the discrimination depicted in the film, as well as how these problems impact the main actors of the film. The findings of the study showed that social class is divided into two: the bourgeoisie is a group of people who have power, an economy, and a good education, while the proletariat is a working class that prioritizes physical work and is a group that experiences difficulties in the fields of economy, education, and problems of power. The impact of social class itself has an impact; pressure between groups, creating hostility, difficulty solving problems, and difficulty upholding justice.Keywords— Social Class, Discrimination, Karl Marx, Bourgeoisie, Proletariat.